2018
DOI: 10.3390/membranes8030080
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of DES-Lignin as a Bio-Based Hydrophilicity Promoter in the Fabrication of Antioxidant Polyethersulfone Membranes

Abstract: Enhancement of membrane permeability at no detriment of its other performances, e.g., selectivity, is a goal-directed objective in membrane fabrication. A novel antioxidant DES-lignin (lignin extracted from birch wood by using a deep eutectic solvent) polyethersulfone (PES) membrane, containing 0–1 wt % DES-lignin, was fabricated with the phase inversion technique. The performance and morphology of the fabricated membranes were characterized by a pure water flux, polyethylene glycol (PEG) retention, Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Furthermore, PES is applied as the main base material for membranes in several membrane separation processes like haemodialysis, purification, extraction and concentration [2]. Despite its many attractive properties, one of the key problems to the widespread use of PES membranes is the proneness to fouling because of its low hydrophilicity [3]. For example, several studies have reported severe fouling tendency of PES-based membrane in the treatment of process waters from the pulp and paper industry, and the biorefinery streams [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PES is applied as the main base material for membranes in several membrane separation processes like haemodialysis, purification, extraction and concentration [2]. Despite its many attractive properties, one of the key problems to the widespread use of PES membranes is the proneness to fouling because of its low hydrophilicity [3]. For example, several studies have reported severe fouling tendency of PES-based membrane in the treatment of process waters from the pulp and paper industry, and the biorefinery streams [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…From another point of view, it seems that even small concentrations of hemicelluloses can affect the formation of the top layer, since, as can be seen in Table 2, there is no large difference in hemicelluloses content between biomass B3 (10.8%) and B4 (6.3%) but the retention values of membranes M3 and M4 are significantly different (70.2 vs 86.1%). Moreover, it has been suggested that lignin can act like a poreformer agent due to the accelerated diffusional rate between solvent and non-solvent caused by the presence of lignin in the casting solution, which might also contribute to the formation of a looser membrane structure when lignin is present in the biomass (Vilakati et al 2015;Esmaeili et al 2018). The FTIR spectrum of M4, shown in Fig.…”
Section: Performance and Chemical Composition Of The Membranes Preparmentioning
confidence: 99%
“…On the other hand, deep eutectic solvents (DES) are considered as a new generation of ILs and have emerged as a biodegradable and renewable green solvent. DES are available at a much lower price [ 53 ], and they can be produced without generating excessive waste. This solvent group has brought comparable physicochemical properties to those of ILs.…”
Section: Sustainability For Employed Solventsmentioning
confidence: 99%
“…In another work carried out by Esmaeili [ 53 ], DES (containing choline chloride and lactic acid in a molar ratio of 1:9) was used to extract lignin. The DES-lignin 0–1% wt mixture was employed as a hydrophilic adhesion promoter to fabricate antioxidant PES membranes by the phase inversion technique [ 53 ]. In this work, NMP was used as the main solvent.…”
Section: Sustainability For Employed Solventsmentioning
confidence: 99%